Post digestion weed seed survival in cattle - Nikolić, Nebojša; Massaro, Selene; Tagliapietra, Franco; Schiavon, Stefano; Masin, Roberta (Frontiers in Plant Science, 2025)
IntroductionThis research aimed to evaluate the impact of ruminant digestion on viability and germination pattern of the seeds of 9 weed species (A. theophrasti, A. myosuroides, A. retroflexus, A. sterilis, C. album, D. stramonium, E. crus-galli, L. multiflorum and S. halepense).MethodsOne hundred seeds of each species were included in nylon bags and exposed to in vitro procedures simulating the rumen fermentation according to an experimental design that considered: 9 weed species, 3 incubation times in the artificial rumen (12, 24 and 48 h), 2 diets (lactating cows, and heifers), 4 replications, plus 4 additional replicas per species with seeds not subjected to the in vitro digestion as a control. This design was repeated two times (2 batches), involving a total of 504 replicas. Results were expressed in relative terms, using the data from the untreated seeds as a scaling factor. Data were analyzed, by species, with a model that considered diet and incubation time, and their interaction as fixed factors, and the batch as a random effect.Results and conclusionsIncubation time evidenced the greatest impact on seed germination and viability (6 species), where diet (4 species) and Incubation time x diet interaction (3 species) had lower impact. Compared to the control, A. theophrasti germination increased to 150% after 12 h but dropped to ~20% after 48 h under the lactating cows’ diet. Germination of A. myosuroides remained stable initially but fell to ~60% after 48 h, while A. sterilis showed consistently low germination, further declining with digestion. Germination of C. album rose to ~130% after 48 h, and the one of E. crus-galli to ~140%. For D. stramonium, germination decreased to ~20%, with heifers’ diet causing greater losses. No significant effects were noted for L. multiflorum, S. halepense, or A. retroflexus. Viability losses were significant for A. theophrasti and A. myosuroides under the lactating cows’ diet and for D. stramonium under the heifers’ diet. Possible variation causes were evidenced in the thickness and the fibrous content (NDF, ADF, ADL) of the seed coats, correlated with the rumen microbial activity.